Electric and dielectric properties of glasses of Cu-Sb-S-I system - Rubish, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
D.c. and a.c. conductivity (d(0) and d(w )) and dielectric parameters (d and tgd ) of Cu-Sb-S-I system glasses are investigated in 1.0*10⁴ - 6.0*10⁷ Hz frequency range and 170-400 K temperature interval. In the glasses of SbSI-CuSbS₂ system the d.c. conductivity along delocalized states prevails. A.c. conductivity is explained by a combinated hopping mechanism of charge transfer by bipolarons and "simple" polarons. A high concentration of charge carriers and availability of dipole structural units Cu⁺S⁻SbS₂/₂ in the glass matrix define dielectric proporties of glasses.